Extent of Students Involvement in Extracurricular Activities and Academic Performance Among Grade 8 Students - . Vispo, Genesis B; Macalinao, Zenvi Ann (Future Science / FSH-PH Publications, 2024)
This research study explored the extent of extracurricular activities on student’s academic performance. The study aimed to address the students’ involvement in extracurricular activities and academic performance. It was conducted among the Grade 8 High School Students of Zambales National High School. This study utilized a descriptive quantitative research design, a survey questionnaire was used as the main research instrument for obtaining data and analyzing quantitative data gathered from the respondents. Based from the findings, it concludes that the majority of respondents were female students aged 13-14 with a middle-income family income. Sports was the most involved, and students did not participate in debates. The level of involvement in extracurricular activities was slightly involved. The students rated satisfactory academic performance. There was no significant difference in involvement based on profile variables or academic performance. The study recommends that secondary schools should consider extracurricular activities as a way to promote student growth and provide experiences outside the classroom. School counselors should work with students to identify activities that align with their interests and skill levels.